The effect of Corporate Social Responsibility (CSR) initiatives on consumer purchasing behaviour: A study on Celcom (Axiata) Berhad / Norasyikin Sofian - Sofian, Norasyikin (2011)
The main purpose of this research is to know the effect of Corporate Social Responsibility (CSR) Initiatives on Consumer Purchasing Behavior : A Study On CELCOM Axiata Berhad. This research has been done at CELCOM Temerloh. There have three independent variables that have been use. Those variables include environment initiatives, children initiatives and health initiatives. The researcher used primary data and also secondary data to perform the research. The primary data used include questionnaire and also personal interview with branch manager CELCOM, Mr Mohd Amin. The secondary data used is books, journals, article, reports and also internet. To perform the findings, the researcher used frequency distribution, reliability analysis, correlation analysis and regression analysis. Regressions analysis and correlation analysis is very important to see the relationship between independent variable and dependant variable. The result shows that there is relationship with all variables